SANKSI HUKUM BAGI PENGEDAR DAN PENGGUNA NARKOBA DIKALANGAN REMAJA - Senandi, Winna Amelia A. (JURNAL PENGABDIAN PAPUA, 2023)
The application of science and technology in the form of counseling with the title "Legal Sanctions Against Drug Users and Dealers for Teenagers in Asei Village" was held in Asei Village, East Sentani District, by consideration that there are groups of school age children and teenagers where they are very vulnerable to drug problems, and these groups respectively represent teenage children as well as school-aged children. The aim of this research and service is to provide an understanding of what drugs are and their types, to understand the regulation of narcotics crimes in statutory regulations and to know and understand efforts to prevent the abuse of narcotics and illegal drugs. The result of this service is that the material provided in the counseling about Legal Sanctions Against Drug Users and Dealers among Teenagers was well received by the counseling participants with indicators of good feedback and response from the participants with various weighty questions asked during counseling takes place in face-to-face form. Finally, it is hoped that counseling regarding the problem of narcotics and illegal drug abuse must be carried out routinely, especially for teenagers and school age children and teenagers as a preventive measure in efforts to prevent and overcome the problem of narcotics and illegal drugs. Keywords: sanctions; law; users; dealers and narcotics